Motivating Employees through Job Design and Compensation: An Observation (Nepalese Journal of Management Research, 2023)
This study aims to examine the relationship and impact of job design and compensation on employee motivation. It is based on primary data obtained by distributing questionnaires to 15 Nepalese business organizations. The results show that job design has a significant positive relationship with employee motivation. In the same way, the results demonstrate that compensation has a significant positive relationship with employee motivation. In fact, employees who think their jobs are well-designed are highly motivated at work. Moreover, employees are highly motivated at work when they perceive a fair and efficient compensation system. Therefore, to enhance employee motivation, organizations must redesign job policies and foster employee trust. They also need to develop trusting compensation and incentive systems for their employees to increase employee motivation.